라이프로깅 애플리케이션 사용성 평가 - 이조은(Joeun Lee); 권지은(Jieun Kwon) (한국콘텐츠학회 논문지, 16(12), 2016)
As user-centered design and content development emerge, the research and the establishment of items on usability evaluation are becoming more important. However, research on usability evaluation for digital systems in specific areas of mobile applications is still incomplete. Due to the recent development of wearable devices and smartphones, development and usage of quantified-self and life-logging applications has been rapidly increasing. This study aims to establish evaluation items and the main factors for the usability assessment of the applications that support life-logging services. In order to establish evaluation factors for life-logging application usability, we first gathered existing usability assessment items and selected the initial items through the Focus Group Interview(FGI). Second, we conducted user assessment surveys on the selected initial questionnaires and performed reliability and exploratory factor analyses based on the survey results. Third, through the statistical analyses results, we established 28 usability assessment items and four factors: recognition; functionality; aesthetics; and satisfaction. Finally, we discussed the expectations and limitations of the established usability assessment. The results from this paper could be used as a guideline for the usability assessment of life-logging applications and thus will contribute to effective content development. 사용자 중심 디자인과 콘텐츠 개발이 대두되면서 사용성 평가에 대한 연구와 항목 정립이 중요해지고 있다. 그렇지만, 모바일 애플리케이션이나 특정 분야에 대한 디지털 시스템에 대한 사용성 평가에 대한 연구는 미비한 상태이다. 최근 웨어러블 기기와 스마트 폰의 발달로 자기 정량화(Quantified-self) 또는 라이프 로깅에 대한 사용과 콘텐츠 개발이 급증하고 있다. 본 논문은 라이프로깅 서비스를 지원하는 애플리케이션에 대한 사용성 평가 항목과 요인을 정립하고자 하는데 있다. 본 연구를 위하여 첫째, 라이프로깅 애플리케이션의 사용성 평가 요인을 정립하기 위하여 기존의 사용성 평가 항목을 수집하고 FGI(Focus Group Interview)를 통해 초기 항목을 선정하였다. 둘째, 선정된 초기 항목에 대한 사용성 평가 설문을 진행하여 그 결과에 대해 신뢰도 분석과 탐색적 요인분석을 실시히였다. 셋째, 통계 분석 결과를 통해 28가지 사용성 평가 항목과 4가지 요인인 인식성, 기능성, 심미성, 만족성을 정립하였다. 마지막으로 정립된 사용성 평가에 대한 활용 기대와 한계점을 논의할 것이다. 본 논문의 결과는 계속 증가하고있는 라이프로깅 애플리케이션의 사용성 평가 시 가이드라인으로 활용되어 효과적인 콘텐츠 개발에 기여할 것이다.